A study to assess the knowledge, practice, and personal hygiene among respondents regarding childhood diarrhoea in a selected area of South Delhi, India: a cross-sectional study - Azam, M.; Amir; Akram, M. (International Journal Of Community Medicine And Public Health, 2025)
Background: Diarrhoeal disease is a leading cause of morbidity and mortality among children under five, particularly in developing countries. Awareness of spreading, preventive measures, and healthy practices such as breastfeeding, immunization, and proper sanitation are essential to reduce this burden. This study aimed to assess knowledge, practices, and personal hygiene regarding diarrhoeal disease among caregivers of under-five children in South Delhi. Methods: A community-based cross-sectional study was conducted from October 2019 to September 2020 among 493 randomly selected households with at least one child under five. A total of 460 respondents who met the inclusion criteria were enrolled. Data were collected using a structured questionnaire on socio-demographics, knowledge, practices, and hygiene. Analysis was done using SPSS version 23 with chi-square tests; p<0.05 was considered statistically significant. Results: Among respondents, 46.3% were aware that tooth eruption is a cause of diarrhoea, while 72.8% and 79.3% attributed unsafe water and food exposed to flies as causes, respectively. Poor knowledge of vaccination was reported by 29.3%. During diarrhoeal episodes, 74.8% of respondents reported using the same or more water, whereas 25% reduced intake. Regarding hygiene, 84.1% practiced hand washing with soap after child’s faeces disposal, 90.7% after defecation, and 44.6% before cooking. Conclusions: The practices of respondents were not proper in spite of their knowledge regarding diarrhoeal disease where whereas personal hygiene was performed better than practices. Therefore, health education should be utilized as a tool to promote knowledge, good practices, and personal hygiene, ultimately reducing morbidity and mortality.